EVOLUTION AND THEODICY: HOW (NOT) TO DO SCIENCE AND THEOLOGY: with Denis Edwards, "Christopher Southgate's Compound Theodicy: Parallel Searchings"; Ted Peters, "Extinction, Natural Evil, and the Cosmic Cross"; Robert John Russell, "Southgate's Compound Only‐Way Evolutionary Theodicy: Deep Appreciation and Further Directions"; Bethany Sollereder, "Exploring Old and New Paths in Theodicy"; Holmes Rolston, III, "Redeeming a Cruciform Nature"; Ernst M. Conradie, "On Social Evil and Natural Evil: In Conversation with Christopher Southgate"; Philip Clayton and Steven Knapp, "Evolution, Contingency, and Christology"; John F. Haught, "Faith and Compassion in an Unfinished Universe"; Celia Deane‐Drummond, "Perceiving Natural Evil through the Lens of Divine Glory? A Conversation with Christopher Southgate"; Nicola Hoggard Creegan, "Theodicy: A Response to Christopher Southgate"; and Neil Messer, "Evolution and Theodicy: How (Not) to Do Science and Theology.". Issue 3 (29th August 2018) - Messer, Neil
Abstract: This article uses Christopher Southgate's work and engagement with other scholars on the topic of evolutionary theodicy as a case study in the dialogue of science and Christian theology. A typology is outlined of ways in which the voices of science and the Christian tradition may be related in a science–theology dialogue, and examples of each position on the typology are given from the literature on evolution and natural evil. The main focus is on Southgate's evolutionary theodicy and the alternative proposal by Neil Messer. By bringing these two accounts into dialogue, some key methodological issues are brought into focus, enabling some conclusions to be drawn about the range and limits of fruitful methodological possibilities for dialogues between science and Christian theology.